Outing Class Melalui Jelajah Lingkungan untuk Mengembangkan Kecerdasan Naturalis Anak Usia 4-5 Tahun - Novida AprilinaNisaFitri; Yupita AyuDesiWulandari (Jurnal Pendidikan Educandum, 2026)
Every child is endowed with unique intelligence, one of which is naturalist intelligence that is essential for growth and adaptation. However, technological advances and easy digital access lead children to interact more with gadgets than with the natural environment. As a result, naturalist intelligence does not develop optimally. This study aims to describe the implementation of outing class learning through environmental exploration to develop the naturalist intelligence of children aged 4–5 years at RA Kusuma Mulia Turus and to identify supporting and inhibiting factors. This research employed a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. Data analysis referred to Miles and Huberman’s model: reduction, display, and conclusion. The findings show that outing class implementation involves planning, implementation, and evaluation stages. Activities included introducing natural objects, plants, and pets; feeding animals; caring for the environment; and recognizing natural phenomena. The results revealed that most children developed naturalist intelligence at the “developing as expected” level. Supporting factors were teacher competence, facilities, assistant teachers, geographical location, and student enthusiasm. Inhibiting factors were limited time allocation, less conducive learning conditions, and weather. This study emphasizes that outing class effectively nurtures children’s environmental awareness and enhances naturalist intelligence from an early age.